Legal Analysis of the Urgency of the Role of Amicus Curiae in Proving Criminal Acts at the Trial Stage - Ibrahim, Mahdi; Soponyono, Eko (UNISSULA Semarang, 2025)
The submission of amicus curiae can be said to be an informal recognition, because it does not yet have a legal basis that clearly recognizes the use of amicus curiae. When implementing his considerations, the judge exercises his authority by providing considerations that are implemented wisely. The judge is considered to always know everything about the law, when the judge does not know then the judge's job is to find out first. The interest of amicus curiae is limited to providing legal opinions or opinions. amicus curiae is not mentioned in the evidence in the Criminal Procedure Code. Because the power of proof lies in Article 183 of the Criminal Procedure Code. This thesis research aims to analyze and describe the role and position of amicus curiae legally in criminal justice regulations in Indonesia and this thesis aims to analyze and describe regulatory updates related to the role of amicus curiae in a criminal justice system that has legal certainty. The research design in this thesis uses a sociological or empirical legal research type. Based on the research conducted in this thesis, it can be seen that the role and position of amicus curiae legally in criminal justice regulations in Indonesia do not yet have legal certainty. The role of amicus curiae is very important in supporting the relevance of the world of justice as a place to realize justice for people who are in litigation amidst the dynamics of society that continue to develop in a complex manner, however, this has not been balanced with clear regulations regarding the position and role of amicus curiae, such a situation clearly results in legal uncertainty for the position and role of amicus curiae in the national criminal procedure law system. Regulatory updates related to the role of amicus curiae in a criminal justice system with legal certainty need to be carried out, by regulating the matter of amicus curiae by adding the definition of amicus curiae in Article 1 of the Criminal Procedure Code and adding to Article 184 of the Criminal Procedure Code regarding amicus curiae statements as one of the evidence in criminal cases, creating a management and supervisory institution for amicus curiae so that the amicus curiae used in criminal trials can be accounted for in terms of quality and professionalism, it is necessary to provide information and announcements regarding the existence of amicus curiae.